Implementasi Qris (Gopay) sebagai Inovasi Pembayaran Digital bagi UMKM Desa Gung Pinto - Jufri Naldo; Fatiya Febina Sitepu; Tasya Nadilla; Alda Andrini (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This study aims to reveal the implementation of QRIS (GoPay) as a digital payment innovation for MSMEs. This research employs a qualitative descriptive approach, utilizing interviews and observations to evaluate the outcomes of the socialization process for the development and implementation of QRIS GoPay. The research location was Gung Pinto Village, with 10 MSME sellers as subjects. The primary data for this study were collected through interviews and observations, with supporting data derived from literature studies in books, articles, and other relevant sources. The results indicate that this activity can bring changes to the welfare, quality, and quantity of MSMEs, as well as the behavior and mindset of MSME sellers regarding the use of QRIS GoPay in Gung Pinto Village. This is evidenced by the satisfaction of the 10 MSMEs, including 6 MSMEs with a high level of satisfaction and 3 with a very high level of satisfaction due to the ease and convenience of the transaction process. The other four MSMEs had a low level of satisfaction, and three had a moderate level of satisfaction, due to initial behavioral and mindset constraints. However, over time, their behavior and mindset towards QRIS GoPay have changed, resulting in effective and comfortable use.